1994
DOI: 10.1007/bf02245054
|View full text |Cite
|
Sign up to set email alerts
|

Sedative, memory, and performance effects of hypnotics

Abstract: The sedative, amnestic, and performance disruptive effects of benzodiazepine (Bz) receptor selective and non-selective hypnotics were studied in 23 healthy, normal subjects, aged 26.8 +/- 1.0 years. Triazolam (0.25 and 0.50 mg), zolpidem (10 and 20 mg) and placebo were administered, double-blind, at bedtime in a repeated measures design. During an awakening 90 min later (at approximate peak concentration of each drug) a 30-min performance battery which included memory, vigilance, and psychomotor tasks was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(49 citation statements)
references
References 11 publications
6
39
4
Order By: Relevance
“…Although effective as hypnotics, benzodiazepines also produce undesirable side effects, such as memory impairment, have durations of action that can lead to drowsiness and functional impairment upon awakening ("next day hangover"), and are associated with dependence and abuse liability (Johnson and Chernik, 1982;Lister, 1985;Roehrs et al, 1994;Woods and Winger, 1995). Consequently, the development of drugs with sedative-hypnotic activity equivalent to the benzodiazepines, but with an improved side effect profile, would be of great benefit in the successful management of insomnia, which itself represents an enormous cost to society (Walsh and Engelhardt, 1999).…”
mentioning
confidence: 42%
“…Although effective as hypnotics, benzodiazepines also produce undesirable side effects, such as memory impairment, have durations of action that can lead to drowsiness and functional impairment upon awakening ("next day hangover"), and are associated with dependence and abuse liability (Johnson and Chernik, 1982;Lister, 1985;Roehrs et al, 1994;Woods and Winger, 1995). Consequently, the development of drugs with sedative-hypnotic activity equivalent to the benzodiazepines, but with an improved side effect profile, would be of great benefit in the successful management of insomnia, which itself represents an enormous cost to society (Walsh and Engelhardt, 1999).…”
mentioning
confidence: 42%
“…If ␣5 subunitcontaining GABA A receptors played a dominant role in the amnesic effects of benzodiazepine site ligands, then one would expect that zolpidem, which has no measurable affinity for this subtype, would be free of amnesic effects. This is not the case, since clinical studies have reported retrograde amnesia with zolpidem (Roehrs et al, 1994) and animal studies clearly show an effect of zolpidem on passive avoidance in the mouse . It seems reasonable to propose that the amnesic effects of hypnotics are inseparable from the hypnosis they produce, which in the case of zolpidem and possibly all benzodiazepine site ligands is most likely a result of positive allosteric modulation at ␣1 subunitcontaining GABA A receptors and not due to a specific interaction with ␣5 subunit-containing GABA A receptors.…”
mentioning
confidence: 44%
“…Digit Span: Digit Span is a subtest of the WAIS-N which measures attention and working memory and has been found to be sensitive to sleep-inducing agents (36,48).…”
Section: Day L Lldrsshere)supporting
confidence: 45%